A Comparative analysis associated to virulence of Pseudomonas syringae pv. garcae, the causative agent of Bacterial Blight of coffee in Kenya - Mwangi, Ithiru J.; Gichuru, E. K.; Masanga, J.; Alakonya, A. E. (Journal of Scientific Agriculture, 2018)
The Pseudomonas syringae pathogen is genetically diverse, presumably due to the adaptation of individual pathovars to suit the environments of their respective host plants. Given the immense damage and yield loss due to BBC disease that is caused by Psg, this study sought to determine the diversity associated to virulence of the PSG isolates on coffee in Kenya. Twelve strains of Psg pathogen were collected from different coffee growing regions in Kenya and characterized using both phenotypic and molecular tools using inoculation via host-pathogen interaction and genomic sequencing. The sequencing was done using 16S ribosomal RNA primers 8 F and 1492 R and sequences were then retrieved for alignment and phylogenetic analysis using MEGA 6 via clustalW. The results correlating the 16S rRNA diversity found in the strains with their virulence by inoculation in 4 different coffee genotypes revealed possible existence of different races of Psg. The study provides new knowledge on the nature of virulence of BBC pathogen and a platform towards breeding for durable resistance in Kenya.